Determination of intrinsic defects of functional KDP crystals with flawed surfaces and their effect on the optical properties. Issue 28 (11th July 2022) - Ding, Wenyu; Cheng, Jian; Zhao, Linjie; Wang, Zhenhua; Yang, Hao; Liu, Zhichao; Xu, Qiao; Wang, Jian; Geng, Feng; Chen, Mingjun
Abstract : Intrinsic defects introduced by manufacturing-induced lateral cracks have a great influence on the laser damage of KDP crystals. VO defects reduce the laser-induced damage threshold and VH defects exacerbate the damage growth under laser irradiation. Abstract : A practically nonlinear optical material, the functional KH2 PO4 (KDP) crystal, has an extremely low laser-induced damage threshold (LIDT) due to manufacturing-induced surface defects. The low LIDT induced by these surface defects of KDP crystals hinders their application in laser fusion facilities. Herein, the effect of intrinsic point defects introduced by manufacturing-induced lateral cracks on laser damage was particularly investigated by a combination of spectral detection ( i.e., photoluminescence, Raman and Fourier transformed infrared spectra) and first-principles calculation. It was determined that the manufacturing-induced lateral cracks would introduce more hydrogen vacancy and oxygen vacancy intrinsic defects than the ideal surface. These intrinsic defects would form cluster-type defects, lowering the LIDT to 6.600 J cm −2 by introducing two defect levels of 2.83 eV and 4.89 eV within the band gap of the KDP crystal. To further investigate the effect of intrinsic defects introduced by lateral cracks on laser-induced damage growth, the transformation of charge states of intrinsic defects under laser irradiation was calculated. Combined with the spectral information of the lateral crack-induced laser damage site and the laser damage growth experiments, it was found that the intrinsic defects of lateral cracks have a large amount of evolution, making the crystal prone to severe damage growth. Overall, the avoidance of such lateral cracks with a large number of intrinsic defects is very beneficial for improving the laser damage resistance of KDP crystals.